Perceptions of Industry and Education Practitioners Regarding the Implementation of Digital Learning in Automotive Engineering - Firdaus, Muhammad Dzaky; Sutarto; Mutohhari, Farid; Suyitno; Nurtanto, Muhammad (Universitas Pendidikan Ganesha, 2024)
Digital learning (DL) in vocational education has become a crucial issue that continues to be developed for innovation, including in the automotive engineering department. However, the problem is related to the relevance of the competencies to be achieved in accordance with industry qualifications. In addition, the stages of DL have not been fully understood by various educational practitioners. This study aims to analyze the perceptions of industry and education practitioners regarding the implementation of DL in automotive engineering (DL-AE). Sixteen key informants were involved in data collection through semi-structured interview techniques. Qualitative data were analyzed thematically with the help of the NVivo 12 Plus Software. The findings in this study are classified into three main aspects, namely activities prior to DL-AE implementation (Pre-DL-AE implementation), activities during DL-AE implementation, and evaluation of the DL-AE program. However, the lack of accessibility tools and the lack of intensive monitoring during the DL-AE was an obstacle that had to be solved. During the implementation of DL-AE, roles and responsibilities are needed which include aspects of facilitating, guiding and teaching material according to the portion. Evaluations regarding adjustments or changes to methods and ensuring equitable accessibility are also special considerations in increasing the effectiveness and efficiency of DL-AE in the future. These results have important implications in the development of digital learning that takes into account the aspects found in this research.